KONSEP DLAMAN DALAM PERBANKAN SYARIAH: SEBUAH TINJAUAN EPISTEMOLOGIS - Munir, Misbahul (Fakultas Ekonomi, UIN Maliki Malang, 2011)
The purpose of this research is to explore the concept of dlaman (the responsibility) in the field of Syariah Banking. The concept refers to business investment based on the principle ofÂ Â profit share. In this sense, joint venture is a running business in which the risk account will be mutually responsible. Furthermore, related to financial loss, the capital loss is not the responsibility for such a manager, this is in the case if the manager is not careless or improper on his/her duty. This research applies the library approach concerning the classical and modern books to construct the concept of dlaman in the field of syariah banking. The result of research indicates that the role of Syariah Banking is not same with the role of mudlarib (investor manager) as the case of conventional mudlarabah (mudlarabah tsunaiyyah). In the classical books, the system of conventional mudlarabah regulates simply for the concept of profit share between two people namely: investor (shohibul mal) and mudlarib. Meanwhile, in fact the syariah banking can be act as mudllarib for saving customer as well as shohibul mal for financing customer. While, the role of Syariah bank to carry out the financial saving for society can be seen as mudlarib intermediary.Â